Parent and Teachers’ Perspectives on Young Children’s Kindergarten Performance Following Play-Based Early Childhood Education - Fyffe, Lisa (International Journal of Educational Studies, 2025)
Play-based learning is highly regarded within early childhood education scholarship and practice, yet American parents and kindergarten teachers report mixed views on play’s relevance in preparing children for academic content in kindergarten. This qualitative, cross-case study explored parent and teacher perspectives on the role of play-based learning in building the kindergarten competency of four children entering kindergarten during the pandemic-affected 2020-2021 school year. Participants were recruited from a Reggio-Emilia-inspired play-based learning early childhood education center located in Northern Colorado and followed over the course of their child’s kindergarten year. Data were collected through a series of semi-structured participant interviews, home visits during remote learning, and artifact collection from school. Yin’s (2018) case-based approach to cross-case research informed the data analysis. Four themes emerged from this research: “In-tune with others”, “I can count on her”, “Appreciates the challenge”, and “Just a good little student”. Participants described the children as socially connected to peers and adults, reliable and independent workers, wanting to be challenged by their schoolwork, and capable of strong academic work across subjects. These findings illustrate how play-based learning equipped the children to navigate the complexities of their kindergartener role from the perspectives of their parents and kindergarten teachers. Early childhood scholars, professionals and parents can use these findings as a salient example of the underlying developmental mechanisms young children draw upon to build their learning dispositions and succeed in school.